Digital Dentistry Applied in Orthodontics: A Bibliographic Review - Garrido Díaz, Macarena (2026)
Developments in digital technologies have transformed dental practice, including orthodontics, by facilitating more accurate diagnoses and personalized treatments. This review aims to evaluate how digital dentistry has impacted diagnosis and planning in orthodontics, highlighting its precision and utility compared to traditional methods. A literature review was conducted following PRISMA guidelines in September 2024. Relevant studies were identified through searches on PubMed and SCOPUS using the keywords “( "orthodontic treatment" ) AND digital AND ( diagnosis OR planning )”. After the inclusion and exclusion criteria were applied, 10 articles were selected for final analysis. The reviewed studies emphasize that digital models are effective tools for orthodontic diagnosis and treatment planning, offering advantages such as reduced clinical time and improved accuracy in simulating dental movements. Technologies, including intraoral scanners and digital setups have shown to be especially effective in handling complex cases. Additionally, the use of CBCT combined with artificial intelligence has enhanced airway evaluation and provided more comprehensive diagnoses. However, the literature also highlights limitations associated with user expertise and variability among different technological systems. The findings of this review support that digital tools in orthodontics offer more precise diagnoses, better treatment planning, and an optimized patient experience. However, implementing these technologies requires overcoming challenges related to the learning curve and system standardization. Future research should focus on addressing these limitations and promoting a smoother integration of digital tools into clinical practice.